2022
DOI: 10.3390/nu14214466
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Bacteria: A Promising Tool for Menopausal Health Management in Women

Abstract: Menopause is a period during which women undergo dramatic hormonal changes. These changes lead to physical and mental discomfort, are greatly afflictive, and critically affect women’s lives. However, the current safe and effective management measures for women undergoing menopause are insufficient. Several probiotic functions of lactic acid bacteria (LAB) have been recognized, including alleviation of lactose intolerance, protection of digestive tract health, activation of the immune system, protection against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 122 publications
(117 reference statements)
1
9
0
3
Order By: Relevance
“…These outcomes support the role of the estrobolome in enhancing health outcomes among peri-and post-menopausal women [10]; [7]. Meta-analysis results indicated that vasomotor and vaginal dryness symptoms were reduced by probiotics to a large effect versus placebo.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…These outcomes support the role of the estrobolome in enhancing health outcomes among peri-and post-menopausal women [10]; [7]. Meta-analysis results indicated that vasomotor and vaginal dryness symptoms were reduced by probiotics to a large effect versus placebo.…”
Section: Discussionsupporting
confidence: 62%
“…β-glucuronidase is the enzyme responsible for deconjugating oestrogen in the gastrointestinal tract and thus increasing levels of the free, bioactive form [8]. Evidence suggests that some probiotics have oestrogen reactivating properties and can modulate β-glucuronidase activities to enable the estrobolome to achieve oestrogen homeostasis [9], [10], [11]. Thus, Chen et al [7] hypothesised that increasing the activity of β-glucuronidase using probiotics may increase the half-life of HRT and effectively decrease the dose that the patient needs to achieve safely effective blood concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the implication of Vm on fertility outcomes and women's health in menopause was explored, given the increasing number of women entering menopause. An emphasis was made on Vm's benefit in the management of menopausal symptoms, reducing the risk of osteoporosis, regulating the nervous system, and lipid profiling for menopausal women[ 11 - 13 ].…”
Section: To the Editormentioning
confidence: 99%
“…Treatment with probiotics to relieve genitourinary sequelae in postmenopausal women (PMW) is a promising option via restoring Lactobacillus abundance in the vagina. Recent evidence shows that oral and direct administration of probiotics in the vagina is an adjuvant therapy to estrogen withdrawal in PMW[ 13 , 24 ].…”
Section: To the Editormentioning
confidence: 99%
“…LAB are commonly isolated from numerous food sources, including kimchi, soybean paste, chili pepper paste, and milk. Interest in isolated LAB is growing worldwide owing to their health benefits, which have been demonstrated in cells, animals, and humans [ 2 - 4 ]. For instance, the combination of Lactobacillus plantarum and tacrolimus monotherapy improves colitis induced by dextran sulfate sodium in mice [ 5 ].…”
Section: Introductionmentioning
confidence: 99%